Strategi Pelayanan Izin Praktek Doketer Pada Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu (DPMPTSP) Kota Pekanbaru - Inda Ayu Nengsih; Herman Herman (Lembaga penelitian dan Pengembangan Masyarakat (LPPM) IAIN Kediri, 2019)
The purpose of this study is to develop a strategy for the practice of permission to practice a doctor at the Office of Investment and Integrated Services One Door (DPMPTSP) Pekanbaru City. This type of research is using descriptive research type with a qualitative method using the SWOT analysis instrument to obtain answers whether it influences the doctor practice permit service strategy at the Office of Investment and One Stop Integrated Services (DPMPTSP) Pekanbaru City. The types of data used in this study are primary and secondary data relating to this research. Sources of data in the study were respondents who provided information related to this study, namely the Head of the Management Division of doctor and employee practice licenses as well as doctors who administered the doctor's practice permit. Data collection techniques carried out by observation, interviews and documentation. The sampling technique is census for employees and purposive sampling for doctor respondents. The strategy that must be carried out by Pekanbaru City DPMPTSP is maximizing employee utilization, innovating in the field of public services, showing commitment to work, improving service quality, providing education and training to employees, providing motivation, strengthening coordination and communication, utilizing technological developments and and so on, where the aim is maximum service to the community specifically to the doctor's practice permit service.